2017
DOI: 10.24247/ijnadec20171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of In2s3 Nanoparticles by Electrochemical Method, Evaluation of its Performance in Photo-Assisted Degradation of Indigo Carmine Dye, Antibacterial and Antimitotic Activity Studies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Thermodynamically, the most stable form is β-In 2 S 3 , which was reported to exhibit exceptional optoelectronic performances [18]. This β form has been widely considered for photocatalysis, photovoltaic systems, antibacterial activity [19][20][21][22], and also as a photosensor material. It has been reported that solar cell devices using β-In 2 S 3 as a buffer layer provide a fractional conversion value close to that of the standard cadmium sulfide (CdS) buffer layer (16.4%) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamically, the most stable form is β-In 2 S 3 , which was reported to exhibit exceptional optoelectronic performances [18]. This β form has been widely considered for photocatalysis, photovoltaic systems, antibacterial activity [19][20][21][22], and also as a photosensor material. It has been reported that solar cell devices using β-In 2 S 3 as a buffer layer provide a fractional conversion value close to that of the standard cadmium sulfide (CdS) buffer layer (16.4%) [23].…”
Section: Introductionmentioning
confidence: 99%